Stem Cell Therapy for Hypoplastic Left Heart Syndrome: Mechanism, Clinical Application, and Future Directions. Issue 2 (6th July 2018) - Bittle, Gregory J.; Morales, David; Deatrick, Kristopher B.; Parchment, Nathaniel; Saha, Progyaparamita; Mishra, Rachana; Sharma, Sudhish; Pietris, Nicholas; Vasilenko, Alexander; Bor, Casey; Ambastha, Chetan; Gunasekaran, Muthukumar; et al.
Abstract : Hypoplastic left heart syndrome is a type of congenital heart disease characterized by underdevelopment of the left ventricle, outflow tract, and aorta. The condition is fatal if aggressive palliative operations are not undertaken, but even after the complete 3-staged surgical palliation, there is significant morbidity because of progressive and ultimately intractable right ventricular failure. For this reason, there is interest in developing novel therapies for the management of right ventricular dysfunction in patients with hypoplastic left heart syndrome. Stem cell therapy may represent one such innovative approach. The field has identified numerous stem cell populations from different tissues (cardiac or bone marrow or umbilical cord blood), different age groups (adult versus neonate-derived), and different donors (autologous versus allogeneic), with preclinical and clinical experience demonstrating the potential utility of each cell type. Preclinical trials in small and large animal models have elucidated several mechanisms by which stem cells affect the injured myocardium. Our current understanding of stem cell activity is undergoing a shift from a paradigm based on cellular engraftment and differentiation to one recognizing a primarily paracrine effect. Recent studies have comprehensively evaluated the individual components of the stem cells' secretomes, shedding new light on the intracellular and extracellular pathways at the center of their therapeutic effects. This research has laid the groundwork for clinical application, and there are now several trials of stem cell therapies in pediatric populations that will provide important insights into the value of this therapeutic strategy in the management of hypoplastic left heart syndrome and other forms of congenital heart disease. This article reviews the many stem cell types applied to congenital heart disease, their preclinical investigation and the mechanisms by which they might affect right ventricular dysfunction in patients with hypoplastic left heart syndrome, and finally, the completed and ongoing clinical trials of stem cell therapy in patients with congenital heart disease.